Answer:
C. (5,1)
Explanation:
Well first we need to single out y in the following equation,
x - y = 4
so,
-x to both sides -y = -x + 4
divide the - by everything y = x - 4.
Now that we have our two equations.
x + y = 6
y = x - 4
We can substitute the y in the x + y = 6 for x - 4
x + x - 4 = 6
2x - 4 = 6
Add the 4
2x = 10
Divide the 2
x = 5.
Now that we have the x we can plug it in for x in x + y = 6
5 + y = 6
-5 to both sides
y = 1
So the solution is (5,1)
For more proof look at the image below.